(x+26)=3(x+6)

Simple and best practice solution for (x+26)=3(x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+26)=3(x+6) equation:



(x+26)=3(x+6)
We move all terms to the left:
(x+26)-(3(x+6))=0
We get rid of parentheses
x-(3(x+6))+26=0
We calculate terms in parentheses: -(3(x+6)), so:
3(x+6)
We multiply parentheses
3x+18
Back to the equation:
-(3x+18)
We get rid of parentheses
x-3x-18+26=0
We add all the numbers together, and all the variables
-2x+8=0
We move all terms containing x to the left, all other terms to the right
-2x=-8
x=-8/-2
x=+4

See similar equations:

| aX300=1,800 | | (y*2)+3+2y=75 | | -194=-4(5-6x)+5x | | 5+8x=x/2+50 | | 2m-15=15 | | 15/x-4=1 | | (X-1)(x+1)=24 | | 10/v-1=4 | | X=3x+2x-x+2x² | | 15-y=-y+8 | | 4x+x^2=484 | | 12=p2+8 | | 28-7x≤=-4(-7x-7) | | X+5+5(2x-7)=x-4-2(2x+3) | | 3x+2x-x+2x²=x | | -a+15=a+6-3 | | 1/4q+2=1/2 | | 12=p2+ 8 | | y-41/2=-33/2 | | -5(1y+-10)=50 | | -2x+310=0 | | 5(1y+-10)=50 | | -2x+310=282 | | 5x-1+9=5x+26 | | 10-2x=x+7-6 | | 550/33=x | | c5=5 | | n3+11=15 | | r+0.12=0.02 | | 1/2n+3=11/6 | | n3+ 11=15 | | 2/3x^2-11/3x-21/3=0 |

Equations solver categories